IRRIGATION IN MODERN ENDODONTICS (World Bulletin of Public Health, 2024)
In the ever-evolving field of endodontics, the role of irrigation has undergone a transformative shift, becoming a cornerstone in modern root canal treatment. This abstract explores the contemporary landscape of irrigation techniques, emphasizing their pivotal contribution to the success and longevity of endodontic procedures. The article navigates through advanced irrigation solutions, including novel irrigants, activation methods, and delivery systems, shedding light on their impact on disinfection, debris removal, and biofilm disruption. Furthermore, the abstract discusses the integration of technology, such as ultrasonic and laser irrigation, into modern endodontic practices. The critical aspects of safety, efficacy, and the potential for minimizing procedural complexities are addressed, highlighting the strides made in achieving optimal root canal disinfection. Through this exploration, the abstract aims to provide insights into the current state of irrigation in modern endodontics and its implications for enhancing treatment outcomes and promoting the longevity of root-filled teeth
Keywords: Irrigation; endodontics; root canal treatment; technology integration